2013
DOI: 10.1890/12-0883.1
|View full text |Cite
|
Sign up to set email alerts
|

Potassium stimulates fungal epidemics in Daphnia by increasing host and parasite reproduction

Abstract: As natural enemies, parasites can dramatically harm host populations, and even catalyze their decline. Thus, identifying factors that promote disease spread is paramount. Environmental factors can drive epidemics by altering traits involved in disease spread. For example, nutrients (such as nitrogen and phosphorus) can stimulate reproduction of both hosts and parasites or alter rates of disease transmission by stimulating productivity and nutrition of food resources of hosts. Here, we demonstrate nutrient-trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 49 publications
(74 reference statements)
2
49
0
Order By: Relevance
“…In Indiana, we sampled host populations in 17 lakes in Greene, Sullivan, and Monroe Counties every week from August to December during the years 2009-2011 (see Civitello et al 2013 for a list of lakes with geographic coordinates). In Michigan, we sampled 15 lakes every other week in Barry and Kalamazoo Counties from 2003 to 2006 (see Cáceres et al 2006 for more details on the lakes).…”
Section: Field Survey: Methods and Resultsmentioning
confidence: 99%
“…In Indiana, we sampled host populations in 17 lakes in Greene, Sullivan, and Monroe Counties every week from August to December during the years 2009-2011 (see Civitello et al 2013 for a list of lakes with geographic coordinates). In Michigan, we sampled 15 lakes every other week in Barry and Kalamazoo Counties from 2003 to 2006 (see Cáceres et al 2006 for more details on the lakes).…”
Section: Field Survey: Methods and Resultsmentioning
confidence: 99%
“…), nutrient availability (Civitello et al . ), chemical contaminants (Civitello et al . ), or predator cues (Duffy et al .…”
Section: Discussionmentioning
confidence: 99%
“…Because it is major constituent of the cytosol and is involved in ion regulation, elevated potassium could affect aquatic biota in different ways. It is generally assumed that potassium limitation is rare [83], but there are instances where enrichment can stimulate the growth of aquatic taxa, including algae [84] and fungal pathogens [85]. In contrast, some studies have suggested the possibility of potassium toxicity.…”
Section: Discussionmentioning
confidence: 99%